2‐(v, k, 1) Designs Admitting a Primitive Rank 3 Automorphism Group of Affine Type: The Extraspecial and the Exceptional Classes. Issue 11 (18th August 2014) - Montinaro, Alessandro
Abstract 2‐(v, k, 1) designs admitting a primitive rank 3 automorphism group <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj2hh5dnkf" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />G=TG0</alternatives>, where G0 belongs to the Extraspecial Class, or to the Exceptional Class of Liebeck's Theorem in [23], are classified.